2021
DOI: 10.1002/mco2.62
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide ameliorates senescence in alveolar epithelial cells

Abstract: Alveolar epithelial cells (ACEs) gradually senescent as aging, which is one of the main causes of respiratory defense and function decline. Investigating the mechanisms of ACE senescence is important for understanding how the human respiratory system works. NAD+ is reported to reduce during the aging process. Supplementing NAD+ intermediates can activate sirtuin deacylases (SIRT1–SIRT7), which regulates the benefits of exercise and dietary restriction, reduce the level of intracellular oxidative stress, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, the metabolic objectives in the proliferative cells mostly consist of growth-boosting metabolites: glycine supports muscle cell proliferation (Jain et al 2012; C. Lin et al 2020), stem cell renewal (Shyh-Chang and Ng 2017), and cancer cell growth (Jain et al 2012), while leucine is associated with protein metabolism, proliferation, and inhibition of apoptosis (Gonçalves and Gomes-Marcondes 2010; Mao et al 2013; Coëffier et al 2011; Xiao et al 2016). Additionally, NMN is a well-known anti-aging metabolite (Mills et al 2016), and is reported to restore cells from senescence, promote proliferation, and increase cell viability (Yamaura et al 2022; Pu et al 2022; Fang et al 2021). These results suggest that our model can infer metabolic objectives and distinguish cells with different proliferation abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the metabolic objectives in the proliferative cells mostly consist of growth-boosting metabolites: glycine supports muscle cell proliferation (Jain et al 2012; C. Lin et al 2020), stem cell renewal (Shyh-Chang and Ng 2017), and cancer cell growth (Jain et al 2012), while leucine is associated with protein metabolism, proliferation, and inhibition of apoptosis (Gonçalves and Gomes-Marcondes 2010; Mao et al 2013; Coëffier et al 2011; Xiao et al 2016). Additionally, NMN is a well-known anti-aging metabolite (Mills et al 2016), and is reported to restore cells from senescence, promote proliferation, and increase cell viability (Yamaura et al 2022; Pu et al 2022; Fang et al 2021). These results suggest that our model can infer metabolic objectives and distinguish cells with different proliferation abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, this study illustrates the difficulty in assessing the systemic efficacy of aging interventions with various regimens, ages, and tissue effects. However, considering the availability of NAD + precursors for the public, the inconsistency in risk and benefit across tissues continues to be concerning (50, 52, 62, 65, 67, 81). The limited regulations around consumption of supplements intended to boost NAD + levels underscore the urgent need for increased caution and further studies in the use of such supplements for public safety.…”
Section: Discussionmentioning
confidence: 99%
“…Some students find out about the grasp of face from the standpoint of psychology, learn about the function of intelligence on face recognition, and assemble two useful fashions of face recognition [8,9]. Others learn about the grasp and cognizance of face from the point of view of physiology or vision.…”
Section: Related Workmentioning
confidence: 99%